MON-546 Drivers of Thyroid Cancer Diagnosis in a Middle-Income Country: An Analysis in a Thyroid Cancer Referral Center in Ecuador - Lincango Naranjo, Eddy (J Endocr Soc, 2019)
Introduction Thyroid cancer (TC) incidence has tripled in the last decades with relatively steady rates of mortality. The growing use of imaging techniques (e.g. neck ultrasound, computed tomography) is a common driver of thyroid cancer diagnosis in the United States and other developed countries. Often, the thyroid cancer lesions found incidentally by imaging are small papillary thyroid cancers of indolent course. However, the triggers that fuel thyroid cancer diagnosis in non-high-income countries is unclear. Ecuador is a middle-income country with the highest thyroid cancer incidence in South America. Our goal is to describe the triggers of thyroid cancer diagnosis in a thyroid cancer referral center in Ecuador and to explore the association of the mechanism of detection with tumor size and histology. Methods In this retrospective cohort study, patients with TC were recruited at a thyroid cancer referral Center in Ecuador between June 1st, 2014 to December 31st, 2017. Triggers of TC diagnosis were collected using a questionnaire, patient’s records, and were classified into: 1) incidentally found (imaging, unrelated test, or histology) in an asymptomatic patient 2) Non-incidental diagnosis (palpable nodule or presence of thyroid nodule related symptoms). Results A total of 452 patients with thyroid cancer were included. Their mean age at diagnosis was 44 (±15) years and 427 (94.5%) of them were female. Thyroid cancer was detected incidentally in 249 patients (55%): 203 (51.3%) by ultrasound, 3(0.7%) by unrelated test, and 13(35) found incidentally in the histologic examination of a thyroid gland removed for a benign condition. In 203 patients (45%), thyroid cancer was found non-incidentally (palpable tumors or symptoms). The mean tumor size of thyroid cancer lesion found incidentally was 1.6 cm (SD 1.2) compared to 3.6 cm (SD 1.8) found non-incidentally, P= 0.001. All micropapillary thyroid cancers, 91 cases, were found incidentally. Conclusion In this thyroid cancer referral center, half of thyroid cancer lesions were found incidentally on patients without symptoms. The main driver of incidental finding was the use of neck ultrasound requested for non-thyroid tumor related symptomatology. Similarly, to what is seen in the United States, our findings suggest the important role of imaging on the possible overdiagnose of thyroid cancer.